Handling excess zeros in count models for recreation demand analysis without apology - Adan Martinez-Cruz (ETH Zurich, CER-ETH - Center of Economic Research, 2016)
Hurdle and zero-in ated models are the two foremost methods used to deal with excess zeros. However, their reliance on the nonparticipation assumption is a drawback when applied to recreation demand analysis because there is not a theoretical framework convincingly explaining presence of non-participants. This paper dis- cusses how latent class count models represent a theoretically consistent alternative to handle excess zeros. The theoretical model behind a latent class model does not require the non-participation assumption. Instead, excess zeros is explained as the accumulation of corner solutions from individuals belonging to different classes.
Keywords: C29; Q26; Q51; 330; Excess zeros; Latent class count models; Travel Cost Method; Nachfrage; Messung; Item-Response-Theorie; Generalisiertes lineares Modell; Theorie